Peningkatan Kerja Sinergis Melalui Pembelajaran Fisika Berbasis Potensi Lokal - Siti Sarah (Department of Physics Education, Universitas Mataram, 2019)
The 21st century is a period of rapid development of information and communication technology. Therefore, various life skills and living values are needed to balance them. One of the living values that is really needed is the synergistic work that can be grown through local potential physics-based learning. This study aims to determine whether there is an increase in student synergistic work through local potential physics-based learning. The research method that will be used is a quasi experiment. The instruments were observation sheets and questionnaires. Data analysis used quantitative and qualitative descriptive analysis. The results showed that there was an increase in synergistic work of students who conducted physics learning based on local potential of 0.52381 with the medium category